소듐락테이트 및 LiNi₀.₆Co₀.₂Mn₀.₂O₂(NCM622) 양극재를 이용한 슈와넬라 푸트레파시엔스의 혐기 조건 호흡에 따른 양극재 금속환원 및 추출 - 박상희(Sang-Hee Park); 정해성(Haesung Jung) (Daehan hwan'gyeong gonghag hoeji, 2024)
목적:폐배터리에서 리튬, 니켈, 코발트, 망간 등의 유가금속 자원을 Shewanella putrefaciens의 혐기성 미생물 호흡을 통해 환원 및 친환경적으로 추출할 수 있는 가능성을 확인한다. 방법:혐기성 조건에서 환경 미생물인 Shewanella putrefaciens를 사용하여 NCM622 양극재(LiNi0.6Co0.2Mn0.2O2)에서 리튬, 니켈, 코발트, 망간의 금속 추출을 시도하였다. 금속 산화물 환원 과정을 모방하여 pH 7.5 조건에서 금속 추출 가능성을 평가하였다. 결과 및 토의:연구 결과, 미생물을 이용한 방법으로 NCM622에 포함된 전체 금속의 약 26%가 중성(pH 7.5) 조건에서 추출 가능함을 확인하였다. 기존의 산성 습식 공정과 달리 추가적인 화학물질 사용 없이 금속 추출이 가능함을 보여주었으며, 환경 시스템에서 발생할 수 있는 중금속 오염 가능성도 정량적으로 평가되었다. 결론:미생물 호흡을 이용한 금속 추출은 리튬 이온 배터리에서 금속을 지속 가능하게 회수할 수 있는 새로운 경로를 제시하며, 환경적 지속가능성을 향상시키는 잠재력을 보여준다. 이 방법은 배터리 폐기물에 의한 중금속 오염 문제 해결에도 기여할 수 있다. Objectives:The objective of this study is to confirm the possibility of reduction and consequent dissolution of Li, Ni, Co, and Mn from NCM622 cathodes in spent Li-ion batteries through the anaerobic respiration with Na-lactate by Shewanella putrefaciens. Methods:The method involves using anaerobic microbial respiration to mimic dissimilatory metal oxide reduction, allowing metals to be leached from NCM622 cathodes (LiNi0.6Co0.2Mn0.2O2) under near-neutral pH conditions (~7.5). Results and Discussion:The results show that approximately 26 wt% of the total Li, Ni, Co, and Mn were successfully leached into the solution within two weeks. This approach differs significantly from conventional acidic leaching processes, offering a more environmentally friendly and sustainable alternative. In addition, we provide quantitative information regarding the dissolution of NCM622 when it is exposed in environmental systems. Conclusion:In conclusion, microbial-based metal leaching presents a novel, sustainable pathway for recovering metals from spent Li-ion batteries, addressing environmental concerns and reducing dependence on traditional energy-intensive recovery methods. KCI Citation Count: 0